Tracheobronchomegaly (Mounier-Kuhn syndrome) and Bronchiectasis as rare manifestations of Homocystinuria - Aasir M. Suliman (14150217) (2023)
Homocystinuria (HCU) is a rare autosomal recessive inherited disorder usually diagnosed in childhood. It is characterized by a deficiency of the enzyme that converts homocysteine to cystathionine. The accumulation of homocysteine leads to abnormalities in the ocular, skeletal, cardiovascular, and central nervous systems. HCU shares several clinical features with Marfan syndrome; however, respiratory system involvement in HCU is uncommon and rarely reported. Bronchiectasis has been previously reported in a few cases of HCU, and it was attributed mainly to fibrillin deficiency. This case describes a young girl diagnosed with classical HCU since childhood who presented with a chronic productive cough and was initially misdiagnosed as bronchial Asthma. However, upon further evaluation, she was eventually diagnosed with tracheobronchomegaly (TBM), or Mounier-Kuhn Syndrome, and bronchiectasis based on the computed tomography (CT) scan of chest findings. To our knowledge, this is the first reported case of TBM and bronchiectasis in HCU. We believe that fibrillin degeneration may be the key to understanding this unusual association in HCU. Other Information Published in: Respiratory Medicine Case Reports License: http://creativecommons.org/licenses/by/4.0/ See article on publisher's website: https://dx.doi.org/10.1016/j.rmcr.2023.101808